The potential of developing heritage based tourism in Kluang, Johor: SWOT analysis - Mohd Paruddin, Nur Faezah; Saad, Mazni (2020)
Kluang is a city that has potential to be developed as one of the heritages based tourism destination in Johor other than Muar. This study is focused on identifying the potential of Kluang to be developed as heritage based tourism using SWOT (Strengths, Weakness, opportunities, and threats) analysis. SWOT analysis data are obtained through qualitative method using interview session with local communities that aged above 18 years old and have stayed in Kluang, Johor for more that 5 years.3 respondents involved in the interview session and provided good co-operation. The findings of the SWOT analysis are identified, Kluang, Johor have the strength of having a unique historical heritage. In terms of weaknesses, some inherited elements are well maintained and there are improvements that need to be improved such as traffic congestion. In addition, Kluang located in the center of the city area caused the area to experience traffic congestion. In terms of opportunities, the authorities have made various efforts to increase the arrival of tourists to the area. In addition, Kluang can further develop as a heritage tourism destination as many heritage elements can attract tourists. Then, the findings of qualitative methods in terms of strengths are that most respondents say the main attraction in Kluang is due to its historical story and the remains of monuments found in the Kluang. In terms of weakness, most respondents said that rapid urban development has affected the heritage development efforts in Kluang. In terms of opportunities, most respondents agreed that Kluang has the potential to be a heritage tourism destination. This will cause many development areas to be affected.